The Idle Fountain - Pericleous, Vicky (My University, 2020)
Art Seen is delighted to present Vicky Pericleous’ solo exhibition titled "The Idle Fountain". The exhibition title is taken from Jorge Luis Borges’ poem ‘Elegia de un Parque’ (Elegy for a Park), from the collection ‘Los Conjurados’ (The Conspirators), of 1985. The exhibition is staged around a series of speculative acts, activated towards a spatial and temporal asynchronicity of hierarchies and narratives. Images and sites re-appear as excesses –performed spectres of post-historical presences?– caught in a contemplative and constant occurrence. An ever but not lasting return. In every return, appearances and proximities differ, destabilizing the – delayed-gaze from the body, which continues to perform in its temporal site. A situation, which might recall the experience of an after-image? Triggered by excess light, the after-image remains, only for less than a second, in the apparent –quasi– gaze that the nervous system produces, while the body is already somewhere else. Could it be then, when experiencing an accentuating situation that the idle gaze, shifts? Opening the possibility towards an-other synchronicity. Of returning in an evocative elsewhere or towards a different mode of engaging with the world(s) and its means of production. Is it not, after all that within these very means of production, certain pathologies can be emerged or be sensed? This rupture emanates from a variant of scenarios. Too much sun. The camera flash. In a Ballardian sense, the alluring blaze of an –imminent– collapse. The exhibition highlights a series of tensions between narratives and contexts, while moving, neither back nor forth, looking neither near nor far, but simultaneously, in images, spaces and sites in and beyond the gallery space. Producing an overlapping of variant scenarios –and proximities– that could, or not, extend in and out of each work. These spatio-temporal acts set up a suggestive system of mobility across spaces and temporalities, as in a meta-geographical approach. The exhibition examines not only these spaces and their representation, but also the space(s) produced between them.
Keywords: Tensions; Images; Spaces; Sites